Study on quality of wastewater from car wash premises - Izzati Syazwani Ahmad Talat (School of Environmental Engineering University Malaysia Perlis, 2011)
Car wash wastewater (CWW) normally contains oil and grease, rubber, paints, phosphate, dust and sand and organic matter. the wastewater runoff from the car anters the gutters gone into the storm water system. The wastewater from storm pollutants end up in our rivers and sea. The objective of this research is to study the waste water quality produced from car wash premises. Therefore, ideal solutions can be suggested to overcome the problem with the simple wastewater treatment such as aeration and adding alum. three car wash premises were selected in area Perlis for this study. The waste water sample was taken from the site at two point such as car washing area and discharge outlet.